A novel electromagnetic biodegradable nanocomposite based on cellulose, polyaniline, and cobalt ferrite nanoparticles. (15th July 2019) - Abou Hammad, A.B.; Abd El-Aziz, M.E.; Hasanin, M.S.; Kamel, S.
Highlights: PANI/Cell/CFO-NPs biodegradable electromagnetic nanocomposites were prepared. Different ratio of CFO-NPs was used during nanocomposites preparation. The prepared nanocomposites showed high antibacterial activity. The magnetic property of the prepared nanocomposites was enhanced by CFO-NPs. Abstract: Biodegradable, antimicrobial, and semiconducting cellulosic composite was synthesized by in - situ polymerization of polyaniline in the presence of cellulose. The cobalt ferrite nanoparticles (CFO-NPs) were added during the polymerization process to acquire this composite magnetic property. The CFO-NPs were prepared by sol–gel method with average particles size less than 50 nm. The nanocomposites were characterized by Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX). In addition, their magnetic, dielectric constant, dielectric loss, and conductivity behaviors were studied. The magnetization (Ms ) and conductivity increased up to 3.7 emu/g and 3.5 × 10 −3  S/cm, respectively, with increasing CFO-NPs content. The prepared electromagnetic nanocomposite exhibits highly efficient biodegradability and antimicrobial activity against Escherichia coli, Bacillus subtilis, and Candida albicans . The antimicrobial activity increased with increasing CFO-NPs while the biodegradability decreased.